2014
DOI: 10.1002/jor.22573
|View full text |Cite
|
Sign up to set email alerts
|

Massive accumulation of osteoclastic giant cells in rapid destructive hip disease

Abstract: ABSTRACT:The term rapid destructive hip disease (RDHD) designates a rare coxarthropathy characterized by a rapid destruction of the femoral head within a few weeks to several months. The etiology and pathogenesis of RDHD are not understood. The goal of this study was to define the histological and histomorphometric hallmarks of RDHD to provide a basis for a deeper understanding of the underlying mechanisms. Fifteen consecutive RDHD patients (mean age 78.9 AE 6.4 years, 14 females) demonstrated the characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…Despite the first description of synovial giant cells in RA by Grimley and Sokoloff in 1966 [ 21 ], their role in the pathogenesis of OA remains largely unknown. Some recent reports described the presence of these cells in OA synovium [ 22 , 23 ], whereas others report few or none [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the first description of synovial giant cells in RA by Grimley and Sokoloff in 1966 [ 21 ], their role in the pathogenesis of OA remains largely unknown. Some recent reports described the presence of these cells in OA synovium [ 22 , 23 ], whereas others report few or none [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that in the histological sections of patients with vanishing of the femoral head an increased amount of osteoclasts were found which were morphologically altered and there was formation of resorptive giant cell granulomas. 4 A case series study did not found histopathological traceable reason for infection or malignant disease. 5 The pathophysiology of rapid destructive arthritis is not fully understood.…”
Section: Discussionmentioning
confidence: 96%
“…Seitz et al [33] found histomorphometric signs of high bone turnover with vanishing of the femoral head bone stock due to a severe resorptive reaction to osseous debris with a strongly increased number of morphologically altered osteoclasts along with the formation of resorptive giant cell granulomas both in intertrabecular bone marrow and in the synovial membrane. These findings indicate that rapid destructive arthritis of the hip is a distinct entity with massive osteoclast activation being a central hallmark of the pathogenesis; massive synovial proliferation is likely to be the cause of the disease as a trigger for the massive activation of osteoclastic cells [33].…”
Section: Histologymentioning
confidence: 98%
“…These findings indicate that rapid destructive arthritis of the hip is a distinct entity with massive osteoclast activation being a central hallmark of the pathogenesis; massive synovial proliferation is likely to be the cause of the disease as a trigger for the massive activation of osteoclastic cells [33].…”
Section: Histologymentioning
confidence: 98%